Effect of modifiers on thermal behaviour of Se in acid digestates and slurries of vegetables by graphite furnace atomic absorption spectrometry - Rosa, C. R.; de Moraes, M.; Neto, JAG; Nobrega, J. A.; Nogueira, ARA (Elsevier B.V., 2002)
The influence of sample preparation strategy of vegetables on the electrothermal behaviour of Se without and with chemical modifiers such as Pd(NO3)(2), Pd(NO3)(2) + Mg(NO3)(2), Pd(NO3)(2) + Cd(NO3)(2), pre-reduced Pd, Mg(NO3)(2), and Ni(NO3)(2) was investigated. Acid digestates and slurries of vegetables (0.1% m/v in 1% m/v HNO3 + 0.005% v/v of Triton X-100) were used to prepare reference solutions or slurries. For 10 mul of each modifier tested, pyrolysis and atomization temperatures were evaluated using pyrolysis and atomization curves, respectively. Best conditions, such as thermal stability, signal profile, repeatability and sensitivity were attained using Pd(NO3)(2) as chemical modifier. The following heating program (temperature, ramp/hold time) of the graphite tube of the Varian SpectrAA-800Z atomic absorption spectrometer was used: dry step (85 degreesC, 5/0 s; 95 degreesC, 40/0 s; 120 degreesC, 10/.5 s); pyrolysis step (1400 degreesC, 10/3s); atomization step (2200 degreesC, 1/2 s); clean step (2600 degreesC, 2/0 s). This pyrolysis temperature is 800 degreesC higher than when measuring without any modifier. For 20 muL sample volume and 10 mug Pd(NO3)(2), analytical curves in the 3.0-30 mug Se 1(-1) range were obtained. The method was applied for Se determination in acid digestates and slurries of 10 vegetable samples and one standard reference material (rice flower) and results were in agreement at 95% confidence level. Recoveries varied from 89 to 95% for spiked samples. The lifetime of the graphite tube was ca. 250 firings and the relative standard deviations (n = 12) for a typical acid digestate and slurry containing 20 mug Se 1(-1) were 3.8% and 8.3%, respectively. The limits of detection were 2.0 mug Se 1(-1) and 0.6 mug Se 1(-1) Se for digestates and slurries, respectively. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: selenium; plant materials; slurries; electrothermal atomic absorption spectrometry